The Influence of Maxim Online Transportation Service Quality on Consumer Satisfaction in Bentas, Nusaniwe District, Ambon City - Papilaya, Josef; Sahusilawane, Stevie; Latupeirissa, Juan J (Universitas Pattimura, 2025)
This study investigates the impact of online transportation service quality, specifically Maxim, on customer satisfaction in Bentas, Nusaniwe District, Ambon City. The development of information and communication technology has significantly influenced various sectors, including transportation. Maxim, a Russian-based ride-hailing service, entered the Indonesian market in 2018 and has rapidly gained popularity, particularly due to its competitive pricing and user-friendly application. In Bentas, Maxim's services have gained traction, offering affordable rates compared to other competitors like Gojek and Grab. However, the influence of service quality on customer satisfaction in Ambon, particularly in Bentas, remains underexplored, prompting this research. The research aims to assess the extent to which Maxim’s service quality influences customer satisfaction. The study employs quantitative analysis using regression analysis to explore the relationship between service quality and customer satisfaction. Findings reveal that service quality significantly impacts customer satisfaction, with an increase of 1 unit in service quality leading to a 0.381 unit increase in customer satisfaction. This research is vital as it provides deeper insight into how service quality, which includes aspects such as reliability, responsiveness, assurance, and empathy, directly influences customer experience. Maxim is encouraged to further improve service quality to enhance customer satisfaction in Bentas, Nusaniwe District, Ambon City.